Relación diámetro - altura comercial en el crecimiento de las plantas de Hymenaea oblongifolia Huber "azúcar huaillo" en diferentes muestras en bosque natural Puerto Almendra, Loreto, Perú - 2021 - Ayarza Zuñiga, Armando (2022)
The research work was carried out in a natural forest of CIEFOR Puerto Almendra - FCF - UNAP, San Juan Bautista district, Maynas province, Loreto region. The objective was to determine the degree of relationship between the diameter and commercial height in the growth of Hymenaea oblongifolia Huber plants in different samples in natural forest. Puerto Almendra, Loreto, Peru - 2021. The variables evaluated were the diameter and commercial height of the trees of the species under study with DAP ? 10 cm; the samples were, Sample 1 (M1) = 39 data distributed in 2 diameter classes; Sample 2 (M2) with 52 individuals distributed in 4 diameter classes; Sample 3 (M3) = with 59 individuals distributed in 6 diameter classes and the Representative Sample with 63 individuals without diameter classes. The results of the diameter- commercial height relationship indicate that the cubic allometric model was the one with the best fit, and the degree of relationship between the variables was fair to good; The equations for the prediction of the diameter- commercial height relationship are: Sample 1: Y= - 13.632 + (2.206 x t) + (0.000 x t2) + (- 0.003 x t3); Sample 2: Y= -10.823 + (2.652 x t) + (-0.119 x t2) + (0.002 x t3); Sample 3: Y= -7.545 + (2.090 x t) + (-0.090 x t2) + (0.001 x t3); Representative Sample: Y= 2.490 + (0.354 x t) + (0.002 x t2) + (0.000 x t3).